FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA DOSEN TETAP DI STIKES HARAPAN IBU JAMBI TAHUN 2022 - Anggini, Agnes; Cici Wuni; Subakir, Subakir (Jurnal Cakrawala Ilmiah, 2023)
The function of a lecturer is to carry out the tri dharma of higher education, namely education and teaching, research and community service. In addition to carrying out the tri dharma of higher education, lecturers at STIKes Harapan Ibu Jambi do other tasks. The many demands of roles and tasks that must be carried out by a lecturer will have an impact on work stress. The purpose of the study was to find out the factors related to work stress in permanent lecturers at STIKES Harapan Ibu Jambi. This research is a quantitative research with a cross-sectional approach. The study population was all permanent lecturers of STIKES Harapan, Mrs. Jambi with a total sample of 36 people. The sampling technique uses purposive sampling technique. The research instrument is a questionnaire. Data collection techniques use questionnaires. The data were analyzed univariately and bivariately using the chi square test. As many as 55.6% of respondents experienced low work stress , 50.0% of respondents had poor interpersonal relationships, 36.1% of respondents had boring work routines, 100% of respondents had an appropriate sks workload, 36.1% of respondents stated that they were unsatisfactory with career development. Bivariate results show that there is an interpersonal relationship (p = 0.020) with work stress in lecturers. There is no relationship between work routines, sks workload and career development with work stress in lecturers (p>0.05). For this reason, it is recommended that the institution adjust the workload received by a lecturer to the abilities or capacities possessed by the lecturer. Lecturers are expected to maintain good communication, a conducive work environment, and a close sense of family.